Developmental and Nutritional Dynamics of Malpighian Tubule Autofluorescence in the Asian Tiger Mosquito Aedes albopictus - Croce, Anna Cleta (2023)
Malpighian tubules (MTs) are arthropod excretory organs crucial for the osmoregulation, detoxification and excretion of xenobiotics and metabolic wastes, which include tryptophan degradation products along the kynurenine (KYN) pathway. Specifically, the toxic intermediate 3-hydroxy kynurenine (3-HK) is metabolized through transamination to xanthurenic acid or in the synthesis of ommochrome pigments. Early investigations in Drosophila larval fat bodies revealed an intracellular autofluorescence (AF) that depended on tryptophan administration. Subsequent observations documented AF changes in the MTs of Drosophila eye-color mutants genetically affecting the conversion of tryptophan to KYN or 3-HK and the intracellular availability of zinc ions. In the present study, the AF properties of the MTs in the Asian tiger mosquito, Aedes albopictus, were characterized in different stages of the insect’s life cycle, tryptophan-administered larvae and blood-fed adult females. Confocal imaging and microspectroscopy showed AF changes in the distribution of intracellular, brilliant granules and in the emission spectral shape and amplitude between the proximal and distal segments of MTs across the different samples. The findings suggest AF can serve as a promising marker for investigating the functional status of MTs in response to metabolic alterations, contributing to the use of MTs as a potential research model in biomedicine.